Foreign Exchange Intervention in Emerging Markets: A Survey of Empirical Studies - Lukas Menkhoff (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2012)
Nowadays foreign exchange interventions occur in emerging market economies whereas empirical studies on interventions mainly refer to advanced economies. However, interventions in emerging markets are different from those in advanced economies: they occur regularly and central banks have considerable leverage, derived from relatively high reserves, some non-sterilization, the central bank's information advantage and capital controls. Consequently, these interventions often successfully impact the level and volatility of exchange rates. Nevertheless, more research on interventions in emerging markets is needed analyzing the influence of heterogeneous institutional circumstances, examining the role of central bank communication and using high-frequency data.
Keywords: F31; E58; O23; 330; foreign exchange; central bank intervention; emerging markets; transmission channels